EQUITY AND INCLUSION IN REMOTE EDUCATION: UNEARTHING DISPARITIES, INTERROGATING STRATEGIES - TAN , Ali Rıza; KILINÇ , Mustafa; YILDIZ, Münür; BALTA , Murat (SSD Journal, 2023)
This systematic review undertakes a comprehensive examination of the issue of equity and inclusion within the domain of remote education, a domain accentuated by the exigencies of the global COVID-19 pandemic. Through a meticulous analysis of extant scholarly literature, the present study unveils pronounced disparities in access to remote educational resources, delineating determinants that encompass socioeconomic strata and degrees of digital literacy. An integral facet of this exploration involves an in-depth inquiry into the manifold ramifications of these inequities upon historically marginalized demographics, with particular regard to the intricate interplay of variables such as ethnicity, gender, and disability. The review proceeds to elucidate efficacious interventions, strategies, and policy paradigms that have been promulgated to ameliorate these prevailing disparities. By elucidating instances of pedagogical innovation and institutional reform, this study proffers an invaluable compendium of insights tailored for the enrichment of educators and policymakers alike. In proffering a nuanced investigation at the nexus of technology-mediated education and the imperatives of social equity, this systematic review emerges as a critical instrument that augments the ongoing discourse encompassing the evolution of remote learning modalities, underpinned by an imperative commitment to principles of inclusivity and justice.